The complexity of preservice teachers doing an interdisciplinary statistics project - Lekaus, Silke; Meaney, Tamsin; Shockey, Tod (Universitas Papua, 2022)
In this article, 30 preservice teachers’ engagement in an interdisciplinary project about the settlement of Iceland by the Vikings is investigate. A qualitative research method was applied to examine photos that documented preservice teachers’ group work over three days and their responses to an open-ended questionnaire about their learning outcomes. The preservice teachers’ responses to the questionnaire suggested that they failed to recognize the statistical aspects that they had engaged with, such as averages, which could be identified in photographs of their group work over three days. The photographs showed that students had participated in the different cycles of the statistical enquiry model, at least to some degree, with one major lack being variation. These results have implications for teacher educators who want to support preservice teachers to adopt interdisciplinary projects in their future classrooms.